E2F function in muscle growth is necessary and sufficient for viability in Drosophila - Zappia, Maria Paula (Nat Commun, 2016)
The E2F transcription factor is a key cell cycle regulator. However, the inactivation of the entire E2F family in Drosophila is permissive throughout most of animal development until pupation when lethality occurs. Here we show that E2F function in the adult skeletal muscle is essential for animal viability since providing E2F function in muscles rescues the lethality of the whole-body E2F-deficient animals. Muscle-specific loss of E2F results in a significant reduction in muscle mass and thinner myofibrils. We demonstrate that E2F is dispensable for proliferation of muscle progenitor cells, but is required during late myogenesis to directly control the expression of a set of muscle-specific genes. Interestingly, E2f1 provides a major contribution to the regulation of myogenic function, while E2f2 appears to be less important. These findings identify a key function of E2F in skeletal muscle required for animal viability, and illustrate how the cell cycle regulator is repurposed in post-mitotic cells.